OLD WINE IN A NEW BOTTLE: TRADE OPENNESS AND FDI FLOWS—ARE THE EMERGING ECONOMIES CONVERGING?. (10th September 2015) - Apergis, Nicholas; Cooray, Arusha
Abstract : This study uses the club convergence methodology of Phillips and Sul (2007) for emerging economies spanning the period 1960–2013 to explore whether such convergence exists and whether the increase of international trade and foreign direct investment (FDI) flows has been a global or club phenomenon. We find the absence of a homogeneous convergence club. The results for FDI outflows also reach similar conclusions, suggesting the formation of convergence clubs by stage of development. These results suggest that policies that promote convergence in trade openness and FDI flows would permit countries to benefit from mutual interactions and by greater consistency and efficiency in trade regimes, thus permitting these countries to benefit from openness leading to a race to the top rather than bottom. ( JEL F41, C33)